PENGARUH FAKTOR FUNDAMENTAL DAN MAKRO EKONOMI TERHADAP PROFITABILITAS BANK: STUDI EMPIRIS PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 - 2020 - Dwiningtyas, Citta Indiarti; Yoewono, Harsono (Universitas Multimedia Nusantara, 2023)
Abstract” This study aims to analyze the capital adequacy ratio, non-performing loans, operating income operating expenses, loan to deposit ratio, firm size, net interest margin, DPK, inflation, and the exchange rate on bank profitability. This type of research is associative research. The data used for this research is data sourced from the financial statements of commercial banks that are listed consecutively on the Indonesia Stock Exchange (IDX) period 2016-2020. The type of data taken is banking financial statements. The data was obtained from the official website of the Indonesia Stock Exchange (IDX). The data obtained from the research results were analyzed using a regression analysis model with the help of the Eviews 10 program. The results showed that only the CAR, NPL, and NIM variables had a significant influence on the return on assets of commercial banks listed on the Indonesia Stock Exchange period 2016 – 2020. This is in accordance with the provisions because sufficient capital, a decrease in the number of non-performing loans, and a high level of bank effectiveness in managing company assets will be able to increase profitability. Then the BOPO, LDR, firm size, DPK, inflation, and exchange rate variables cannot have a significant effect on the return on assets of commercial banks listed on the Indonesia Stock Exchange period 2016 – 2020. Keywords: Capital Adequacy Ratio; Non Performing Loan; Operating Expenses Operating Income; Loan to Deposit Ratio; Firm Size; Net Interest Margin; Third Party Funds, Macroeconomics; Profitability